(3QSGdI EeGe OGQ GdgLQI CHj YHO Gddg eGdc Hf CfS Hf CHj YGeQ GdEUHMi GdJi cJHgG Edi CejQ GdeDefjfs - (3CHh GdMSf Ydj Hf Nda Hf aJhM GdJdeSGfjs ((3Ydi Hf eMeO GdedGM s)
(3ChdgG (B:s
(3MOKfG GdTjN GdEeGe GdYGde GdYGQa GdJbi LeGd GdMaGX eMi GdSfI CHh GdMSf Ydi Hf Nda Hf eYQhQ GHf aJhM GdJdeSGfi GdeYQha HGdchei QVi Gddg Yfg daXkG ai GdYTQ GdChSW ef Pi GdMLI s
(3BNQgG (B:s
(3habfG Gddg hEjGc dWGYJg hLfHfG hEjGc eYGUjI , hNJe dfG hdc HeG jQVjg HQMeJg hUdi Gddg Ydi SjOfG eMeO fHjg hYdi Bdg hUMHg hSde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B3s
(3QhGjI CHh GdaJM fUQ Gddg Hf LeGYI Yf YHO GdQMef Gdjefi HLGeY OeTbs
(3ef bHdgG WaJ ai GdXdGd hai eSJhOY MjK jNUa GdhQbs
(3jdi GdeNWhW CHjGJ ai eOM GdfHi Udi Gddg Ydjg hSde ChdgG s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
Keywords: (3Gdabg GdeGdcjs